2001
DOI: 10.1046/j.1365-3083.2001.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Immune Status in Latvian Chernobyl Clean‐up Workers with Nononcological Thyroid Diseases

Abstract: The aim of the present work was to characterize the immune status of 385 individuals who participated in the 1986±90 clean-up work of the after effects of the Chernobyl nuclear power plant explosion. Fifty-nine Chernobyl clean-up workers developed the most common thyroid diseases; euthyroid nodular and diffuse goiter; 47 healthy blood donors were taken as controls. The levels of immunoglobulins (IgA, IgG and IgM), the numbers of peripheral blood leukocytes, lymphocytes, monocytes, T lymphocytes and their subpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Researchers showed that in the Chernobyl accident, changes occurred in red blood cells, Hb levels, platelet quality and quantity in people exposed to <1 Gy radiation. They also found that the incidence of thyroid cancer and acute leukemia was significantly increased accompanied by an increase in P53 gene mutation among those who were irradiated during their childhood (10)(11)(12), indicating that age, dose, frequency, time and different stages after exposure could significantly affect the quality and quantity of blood cells and the incidence of tumors. The results of the present study indicated that persistent 0.05-0.65 Gy Ir192 did not cause irreversible inhibition or damage of the hematopoietic system in the affected population, and it may be speculated that the human hematopoietic system is effectively able to compensate for the damage caused by persistent 0.05-0.65 Gy Ir192 exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers showed that in the Chernobyl accident, changes occurred in red blood cells, Hb levels, platelet quality and quantity in people exposed to <1 Gy radiation. They also found that the incidence of thyroid cancer and acute leukemia was significantly increased accompanied by an increase in P53 gene mutation among those who were irradiated during their childhood (10)(11)(12), indicating that age, dose, frequency, time and different stages after exposure could significantly affect the quality and quantity of blood cells and the incidence of tumors. The results of the present study indicated that persistent 0.05-0.65 Gy Ir192 did not cause irreversible inhibition or damage of the hematopoietic system in the affected population, and it may be speculated that the human hematopoietic system is effectively able to compensate for the damage caused by persistent 0.05-0.65 Gy Ir192 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study indicated that humoral immunity can be restored in a short time period, and lymphocytes are extremely sensitive to radiation and their self-healing rate is very slow. It has been reported that immune disorders may be sustained for more than 30 years; the IgG, CD4 + , CD8 + and CD16 + levels of individuals involved in the clean-up of the Chernobyl nuclear leak were significantly lowered and thyroid disease was identified in 59 cases in 385 participants (10). However, immune stimulatory and excitatory effects of low-dose irradiation were not observed in the present study, which may be associated with the special nature of the observed population.…”
Section: Discussionmentioning
confidence: 99%
“…Severe disorders of the immune system were observed among Chernobyl NPP accident clean-up workers from Latvia; characteristic late symptoms included leukocytosis, lymphopenia and malfunction of interferon (IFN) system (Kurjâne, 2001;Kurjane et al, 2001). The ability of peripheral blood lymphocytes (PBL) to produce IFNs has been found to be significantly decreased in 65-90% of accident clean-up workers and there was an increased level of circulating IFN in 40% of patients.…”
Section: Immunological Disturbances In Chernobyl Clean-up Workersmentioning
confidence: 99%
“…Since 1994, data have been included in the Latvian State Register of Persons with Occupational Diseases and Persons Exposed to Radiation due to the CNPP Accident maintained by the specialists of the Centre of Occupational and Radiological Medicine (Pauls Stradiòð Clinical University Hospital). On the basis of information collected in the Centre four doctoral theses (Kurjane, 2001;Zvagule, 2004;Reste, 2013;Silova, 2015) and a lot of scientific studies were completed (Bruvere et al, 1995;Churbakova et al, 1996;Eglite et al, 1997;2009;Mironova et al, 1998;Kalnina et al, 2001;2012;2013;2013a;Kumerova et al, 2000;Kurjâne and Soèòevs, 1999;Kurjane et al, 1999;2000;Mazarevica et al, 2000;Mironova-Ulmane et al, 2001;2001a;Petukhov et al, 2011;Reste et al, 2012;2014;Skesters et al, 2005;2006a;2006b;2008;2010;2010a;Viel et al, 1997;Zvagule et al, 2002;. Clinical observations and epidemiological studies among Chernobyl recovery workers showed that these persons suffer from a broad spectrum of different kinds of diseases more seriously than in the non-exposed general Latvian population.…”
Section: Introductionmentioning
confidence: 99%
“…The present studies are part of long-term investigations that were initiated about a decade ago to determine the role of changes in the antioxidant defence system on the development of post-radiation (post-Chernobyl) syndrome in the clean-up workers from Latvia who worked at Chernobyl (Ukraine) following the NPP accident (Č urbakova et al 1998;Kumerova et al 2000;Kalnina et al 2001;Kurjane et al 2001;Mironova-Ulmane et al 2001;Zvagule et al 2002Zvagule et al , 2006Brüvere et al 2003;Eglite et al 2009). The objective of the present study was to establish if there have been long-term systemic changes in the oxidant/anti-oxidant status of these patients that might reflect adaptation to the progression of oxidative stress injury.…”
Section: Introductionmentioning
confidence: 99%